Hubungan Dukungan Orangtua dan Guru dengan Perilaku Seks Bebas pada Remaja di Nusa Tenggara Timur - Maria Elisa Lena Teda; Afrona E.L. Takaeb; Eryc Z. Haba Bunga; Ribka Limbu (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Free sexual behavior is still an issue that often occurs among adolescents because it can cause unwanted pregnancy, early marriage, abortion, sexually transmitted infection and school dropout. Parental and teacher support is very important in preventing free sexual behavior among adolescents. This study aims to analyze the relationship between parental and teacher support with free sexual behavior in adolescents at East Nusa Tenggara. This type of research is quantitative with cross sectional design. The population in this study was all students at a junior high school in East Nusa Tenggara, totaling 442 adolescents and a sample of 80 adolescents was taken using Proportional Random Sampling. Data were analyzed using a Chi-square statistical test with a significance level of p<0.05. The results of the study indicate that parental support in the form of emotional support (p-value=0.028<0.05), appreciation support (p-value=0.015<0.05), information support (p-value=0.001<0.05), instrumental support (p-value=0.026<0.05) and teacher support in the form of emotional support (p-value=0.003<0.05), appreciation support (p-value=0.001<0.05), information support (p-value=0.028<0.05), instrumental support (p-value=0.000<0.05). Thus, it can be concluded that there is a relationship between parental support and teacher support with free sexual behavior among adolescents at East nusa Tenggara. Therefore, parents and teachers need to increase their support and role in preventing free sexual behavior among adolescent.